Safe Removal of the Urethral Catheter 2 Days Following Laparoscopic Radical Prostatectomy. (17th August 2012) - James, Philip; Glackin, Anthony; Doherty, Alan
Abstract : Purpose . To assess the risks and benefits of early urethral catheter removal following laparoscopic radical prostatectomy. Materials and Methods . Between June 2009 and April 2011, 114 patients underwent laparoscopic radical prostatectomy for clinically organ-confined prostate cancer. Candidates for early removal of the urethral catheter were selected intraoperatively on the basis of the integrity of the vesicourethral anastamosis and the ease of recatheterisation. In the selected cohort of patients, the urethral catheter was removed at day 2. Recatheterisation rates within this group were recorded and analysed. Results . Of the 114 patients who underwent laparoscopic prostatectomy, 64 (56%) were deemed suitable for removal of catheter on second postoperative day prior to discharge. The first 20 patients selected for early removal of urethral catheter were covered with a suprapubic catheter inserted at the time of surgery. Out of 64 patients deemed suitable for early removal of urethral catheter, 53 (83%) were able to pass urine without complication. 11 patients (17%) developed urinary retention that necessitated recatheterisation. In all cases, reinsertion of catheter was performed easily and successfully without the need for cystoscopic guidance or adjuncts. Conclusions . Removal of the urethral catheter at day 2 following laparoscopic prostatectomy is a safe procedure in carefully selected patients.